Strategic Planning of Cybersecurity Governance in Supporting National Digital Infrastructure Resilience - Ghina Fauziyyah (International Journal of Social Research, 2025)
The development of digital transformation has increased the dependence of various sectors on national digital infrastructure to support government, economic, and public service activities. This condition is accompanied by an increasing cyber security threat that has the potential to disrupt the stability of a country's information system and digital resilience. Therefore, it is necessary to have strategic planning for integrated cybersecurity governance to ensure the sustainability and security of national digital infrastructure. This research aims to analyze strategic planning of cybersecurity governance and formulate a governance model that can support increasing the resilience of national digital infrastructure. This research uses a qualitative approach with a descriptive-analytical method. Data collection was carried out through interviews, observations, questionnaires, and documentation studies on organizations that manage information systems and digital infrastructure. Data analysis was carried out using a framework analysis approach with reference to information technology governance frameworks such as COBIT and the NIST Cybersecurity Framework. The results of the study show that the implementation of cybersecurity governance in some organizations is still not fully integrated with the organization's strategic planning. The implementation of IT governance frameworks such as COBIT and NIST can help organizations identify cybersecurity risks, improve threat monitoring, and strengthen inter-agency coordination. This research also produces a strategic planning model for cybersecurity governance that emphasizes the integration of organizational strategies, risk management, security technology, and national policies to improve the resilience of national digital infrastructure